Cultural Representation of Vernacular Housing in Melayu Jambi Traditions - Budi Arlius Putra (JOURNAL VISION TECHNOLOGY (V-TECH), 2019)
The study examine the relationship of architecture, conservation and tourism in representing a cultural character. The study in particular assesses a building code which is the product of a collaborative government strategy between tourism planning and cultural conservations. The research directive study focus on approach in tourism planning and regulation in maintaining cultural representation. Study using a casestudy of Jambi, evaluates of legally binding guidelines in maintaining traditional architecture and investigates how local values are resilient to the vernacular identity. The findings indicate that in Jambi there is an emerging transformation towards the commercialization of local cultural products as potential tourism attractions and modernity effects. The study also provide a significant example of how to reach a desirable strategy of conservation, where a pragmatic approach can be complementary to the cognitive framework of local cultures and beliefs.